2022
DOI: 10.1186/s12936-022-04091-z
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of seasonal malaria chemoprevention with enhanced infection prevention and control measures during the COVID-19 pandemic in Nigeria, Burkina Faso and Chad: a cross-sectional study

Abstract: Background Seasonal malaria chemoprevention (SMC) is a WHO-recommended intervention for children aged 3–59 months living in areas of high malaria transmission to provide protection against malaria during the rainy season. Operational guidelines were developed, based on WHO guidance, to support countries to mitigate the risk of coronavirus disease 2019 (COVID-19) transmission within communities and among community distributors when delivering SMC. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…According to the statements provided by caregivers, a high level of adherence to the dosing regimen was observed among the children, with 89.4% taking their second dosage and 80.2% taking their third. These findings are consistent with previous research conducted in Mozambique and Chad by Wharton-Smith et al [11] and Ward et al [15], who assessed adherence using caregiver testimonies. The high level of adherence may be attributed to the fact that the SMC drugs were well tolerated by the children.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…According to the statements provided by caregivers, a high level of adherence to the dosing regimen was observed among the children, with 89.4% taking their second dosage and 80.2% taking their third. These findings are consistent with previous research conducted in Mozambique and Chad by Wharton-Smith et al [11] and Ward et al [15], who assessed adherence using caregiver testimonies. The high level of adherence may be attributed to the fact that the SMC drugs were well tolerated by the children.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, while the program is well received, distributors need to adhere to the recommended dosage and maintain communication with caregivers to emphasize the importance of taking medications as prescribed on subsequent days, potential adverse events, and appropriate actions to take if they occur [7,21,32]. However, our data suggest that only 66% of caregivers reported starting the first dose while the distributor was directly observing the patient, indicating that distributors may have left the entire blister pack in the house with instructions for a later caregiver to administer the medication, as observed in Mozambique, Burkina Faso, and Chad [10,11,15]. In a qualitative study by Kajubi et al [18], CHWs attributed this inconsistency to their heavy workload, which prevented them from returning to the home later in the day to ensure that they could administer the medication while the child was present.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In Nigeria, Burkina Faso, Chad and Zimbabwe, the community's engagement in malaria campaigns was restricted due to COVID-19. For example, Ward et al (2021), reported difficulty implementing door-to-door delivery of SMC (A23). Furthermore, lack of political will was one of the challenges of malaria elimination strategies (A13).…”
Section: Acceptabilitymentioning
confidence: 99%
“…While this approach had many advantages, such as building caregivers' capacity to administer the remaining doses of AQ, several challenges arose. A previous study conducted by Malaria Consortium in 2020 found that some caregivers refused to administer SMC medicines to their children or did not administer them correctly (7). To address the challenges associated with, and nd local existing solutions to, improve SPAQ administration within selected communities, the role model approach was designed, implemented and evaluated to optimise administration in Burkina Faso, Chad and Togo.…”
mentioning
confidence: 99%